Strength Characteristic of Lightweight Modular Block (LMB) Element using Stabilized Dredged Soil-EPS - Nurul Marfuah; Tri Harianto; A. B. Muhiddin; Rita Irmawaty (Salehan Institute of Higher Education, 2023)
For several decades, lightweight material applications have been extensively studied. Modifying various types of soil with EPS beads or lightweight geomaterials is an alternative construction material on site that can reduce excessive problems such as large deformation and lateral pressure. This study aims to examine the strength characteristics of lightweight geomaterials, namely lightweight modular block/LMB. LMB is composed of EPS beads, dredged soil, and cement. The cement amounts are 3%, 5%, 7%, and 9%, with EPS variations of 0.5% and 0.75% to the mixture weight. Laboratory tests were conducted to investigate the strength with unconfined compression and undrained direct shear tests. Before testing, the specimens were made using the one-layer static compaction method and were cured for 7, 14, and 28 days. This paper also presents explanations related to the specimens making and treatment by providing preliminary test results to compare the effectiveness of the three-layer and one-layer methods. Moreover, the curing treatments to avoid cracking were explained explicitly. The result shows linearity between both increasing the amount of cement and adding more curing time to the increase of the strength parameter. In contrast, adding more EPS decreased the strength, but adding cement helped increase the strength parameter with a remarkable value at C7% and C9%. Increasing the amount of EPS also reduced the density of the mixture by 18%–29%. Doi: 10.28991/CEJ-2023-09-03-014 Full Text: PDF